THE INFLUENCE OF PRINCIPAL LEADERSHIP, TEACHER PERFORMANCE, AND FACILITIES AND INFRASTRUCTURE ON STUDENT ACHIEVEMENT AT SMAN 1 SUNGGAL - Najiris Saleh Siregar; Muhammad Toyib Daulay (RADJA PUBLIKA, 2025)
This study aims to determine and test the influence: (1) the leadership of the principal affects the performance of teachers; (2) Whether the principal's leadership affects the school infrastructure; (3) Whether the principal's leadership affects student learning achievement; (4) Whether the teacher's performance affects student learning achievement; and (5) Does infrastructure affect student learning achievement. The research population was students at SMA Negeri 1 Sunggal, North Sumatra Province with a sample of 235 students. The research method is a quantitative method with Smart-PLS analysis. The results of the study concluded: (1) the leadership of the principal had an effect on teacher performance by 51.8%; (2) the leadership of the principal has an influence on school infrastructure by 47.8%; (3) the leadership of the principal affects student learning achievement by 22.4%; (4) teacher performance affects student learning achievement by 24.7%; and (5) school infrastructure affects student learning achievement by 47.5%. Overall, the results showed that student learning achievement was influenced by the principal's leadership moderated by teacher performance and school infrastructure facilities by 53.4%; while the remaining 46.6% is determined by other factors.